Exploration of The Use of Waqf Assets at Educational Institutions - Arridha Harahap; Yurmaini Yus (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2022)
The research is motivated by several studies that only focus on the use of the waqf system, while the success in managing waqf assets so that the principal and benefits can last is to formulate specific targets for the right needs in using waqf assets. The purpose of this study is to explore the use of waqf assets given to educational institutions so that they are right on target and maintain the essence of the use of waqf assets. The approach used is a qualitative approach using literacy studies from various existing publications. Educational institutions can regulate waqf governance according to the type of waqf property provided by the waqf. The results of this study can provide views for waqf-based educational institutions to be able to maintain and manage waqf assets in accordance with established rules. Mobile waqf such as cars, cash, and securities can be managed by investing in SMEs located around the institution, or rented out or invested in short and medium-term investment programs. Immovable waqf can be managed by building educational facilities or renting out land to produce and all such governance must be in accordance with Islamic finance principles. Immovable waqf can be managed by building educational facilities or renting out land to produce.